2013
DOI: 10.1002/ls.1219
|View full text |Cite
|
Sign up to set email alerts
|

Influence of structural variations on imidazolium‐based ionic liquids

Abstract: In this work, a fundamental study of ionic liquids (ILs) is shown. The main goal was to establish relationships between rheological and tribological properties of ILs and to understand how these properties are linked to the molecular structure of ILs. Of particular interest were the effects occurring to a frictional system due to variations of the anions and the alkyl chain length of the imidazolium-based cations. Tribological experiments were performed using a reciprocating ball-on-disc test machine. To under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Although these compounds are subjected to strong Coulombic interactions, they are liquid over a wide range of temperature (from well below 0 °C to hundreds of Celsius degrees) 1,2 . Although these compounds are subjected to strong Coulombic interactions, they are liquid over a wide range of temperature (from well below 0 °C to hundreds of Celsius degrees) 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Although these compounds are subjected to strong Coulombic interactions, they are liquid over a wide range of temperature (from well below 0 °C to hundreds of Celsius degrees) 1,2 . Although these compounds are subjected to strong Coulombic interactions, they are liquid over a wide range of temperature (from well below 0 °C to hundreds of Celsius degrees) 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the work relating to ionic liquids as a lubricant fluid was dedicated to the problem of the lubrication of steel/steel contact surfaces, as well as to the lubrication of other types of contact surfaces . In these studies, the ionic liquids were used as neat lubricants or as additives to conventional oils . The most commonly used ionic liquids in tribological research were those containing an imidazolium cation and a PF 6 or BF 4 anion .…”
Section: Introductionmentioning
confidence: 99%
“…ILs have been a growing field of tribological research for many years. Studies on ILs focus on their practicability as neat lubricant and as additive in base oils 34‐39 . For a turbine oil, Kronberger et al identified a promising IL as additive to improve the tribological properties 40 .…”
Section: Introductionmentioning
confidence: 99%